Precision medicine in the treatment of primary immunodeficiency diseases. Issue 2 (April 2018) - Leiding, Jennifer W.; Ballow, Mark
Abstract : Purpose of the review: Since the 1990s with the advances in molecular biology, a number of genetic defects have been described. The International Union of Immunological Sciences has recently updated the classification of genetic defects associated with primary immune deficiencies that now number 354. With the ever-expanding list of new monogenic disorders and a better understanding of the immunobiology and function of these defective genes, new therapies have emerged particularly aimed at the autoimmune and inflammatory conditions that plague these patients. Recent findings: Immune deficiencies associated with gain-of-function (GOF) mutations are a potential category for targeted therapies to control the GOF activities of the mutated gene. In addition to the increased susceptibility to infections these patients have autoimmune and inflammatory diseases that are difficult to control with conventional therapies. The dysregulated immune functions of the activated phospholipase-3-kinase δ syndrome, cytotoxic T lymphocyte-associated antigen-4 haploinsufficiency, lipopolysaccharide-responsive beige-like anchor deficiency, the GOF mutations of signal transducer and activator of transcription 1 and 3 immune deficiencies will be reviewed. The targeted therapies for each of these immune deficiencies using small molecule kinase inhibitors and fusion protein biologic modifiers will be described. Summary: In this review, we explore the recent advances in precision medicine treatment of several primary immunodeficiency syndromes in which immune dysregulation is a key feature. Understanding the immunobiology associated with these GOF mutations has led to the use of biologic therapies to better control the associated autoimmune and inflammatory manifestations.